Elucidating Genes and Transcription Factors of Human Peripheral Blood Lymphocytes Involved in the Cellular Response upon Exposure to Ionizing Radiation for Biodosimetry and Triage: An In Silico Approach - Gollapalli, Pavan; Radhakrishna, Vishakh; N., Suchetha Kumari; Gnanasekaran, Tamizh Selvan (Journal of Health and Allied Sciences NU, 2024)
Background Gene expression–based biodosimetry is a promising method for estimating radiation dose following exposure. A panel of highly radio-responsive genes in human peripheral blood was used in the current investigation to create and evaluate a unique gene expression–based radiological biodosimetry method.Methodology In human cellular research, we reviewed the literature on genes and proteins correlating to radiation response in vivo and in vitro. We looked at two publicly accessible independent radiation response gene expression profiles (GSE1977 and GSE1725) and identified the differentially expressed genes (DEGs).Results The obtained data exhibited 42 genes with substantial differential expression, 25 of which were upregulated and 17 of which were downregulated in ionizing radiation exposure groups compared with control groups. The gene ontology enrichment analysis revealed that the hub genes are significantly involved in the regulation of the mitotic cell cycle phase transition, regulation of the mitotic cell cycle, and mitotic cell cycle checkpoint signaling. Out of the 42 DEGs, four top genes (CDK1, CCNB1, UBC, and UBB) were obtained through network centrality features. However, the multicomponent filtering procedure for radiation response genes resulted in cyclin-dependent kinase 1 (CDK1) as a critical gene in the dataset curated.Conclusion Our findings suggest the possibility of discovering novel gene connections involved in the cellular response of human peripheral blood lymphocytes upon exposure to ionizing radiation.
Keywords: radiation; differentially expressed genes; CDK1; gene ontology; peripheral blood